Enhanced Photoactivity of Fe + N Codoped Anatase-Rutile Nanowire Film under Visible Light Irradiation - Kewei Li; Haiying Wang; Chunxu Pan; Jianhong Wei; Rui Xiong; Jing Shi (International Journal of Photoenergy)
Rutile-anatase phase mixed codoped TiO2 nanowires were designed and prepared by a two-step anodic oxidation method. The results of X-ray diffraction, scanning electron microscopy, and high-resolution transmission electron microscopy confirm that the prepared codoped TiO2 nanowires exhibit intimately contacted anatase-rutile heterostructure with the rutile content of 21.89%. The X-ray photoelectron spectroscopy measurements show that nitrogen and iron atoms are incorporated into the titania oxide lattice, and the UV-visible absorption spectra show that the codoping of iron and nitrogen atoms could extend the absorption to visible light region. The photocatalytic activities of all the samples were evaluated by photocatalytic degradation of methylene blue under visible light irradiation. The codoped sample achieves the best response to visible light and the highest photocatalytic activities. The enhancement of photocatalytic activity for codoped sample should be ascribed to the synergistic effects of codoped nitrogen and iron ions and the anatase-rutile heterostructure.